SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Review: Powdery Scab of Potato—Increased Knowledge of Pathogen Biology and Disease Epidemiology for Effective Disease Management - U. Merz; R. E. Falloon (Potato Research, 2009)

Variation for neutral markers is correlated with variation for quantitative traits in the plant pathogenic fungus Mycosphaerella graminicola - J. ZHAN; C. C. LINDE; T. JÜRGENS; U. MERZ; F. STEINEBRUNNER; B. A. McDONALD (Molecular Ecology, 2005)
We compared genetic variation and population differentiation at RFLP marker loci with seven quantitative characters including fungicide resistance, temperature sensitivity, pycnidial size, pycnidial density, colony size, percentage of leaves covered by pycnidia (PLACP) and percentage of leaves covered by lesions (PLACL) in Mycosphaerella graminicola populations sampled from four regions. Wide variation in population differentiation was found across the quantitative traits assayed. Fungicide resistance, temperature sensitivity, and PLACP displayed a significantly higher Q ST than G ST , consistent with selection for local adaptation, while pycnidial size, pycnidial density and colony size displayed a lower or significantly lower Q ST than G ST , consistent with constraining selection. There was not a statistical difference between Q ST and G ST in PLACL. We also found a positive and significant correlation between genetic variation in molecular marker loci and quantitative traits at the multitrait scale, suggesting that estimates of overall genetic variation for quantitative traits in M. graminicola could be derived from analysis of the molecular genetic markers.

Improved immunological detection of Spongospora subterranea - U. Merz; J. A. Walsh; K. Bouchek-Mechiche; Th. Oberhänsli; W. Bitterlin (European Journal of Plant Pathology, 2005)

The potential for the Rapid Screening of Potato Cultivars (Solanum tuberosum) for Resistance to Powdery Scab (Spongospora subterranea) using a Laboratory Bioassay - U. Merz; V. Martinez; R. Schwärzel (European Journal of Plant Pathology, 2004)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)